PEMBELAJARAN BERBASIS SCHOOLOGY UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR MAHASISWA INSTITUT AGAMA KRISTEN NEGERI (IAKN) KUPANG - Yandri Yusuf Cornelis Hendrik; Hendrik A. E. Lao (Jurnal Dedikasi Pendidikan, 2021)
This study aims to analyze the implementation of the schoology application to improve student learning independence for ease and access, effectiveness and efficiency as well as being creative and innovative in the learning process of the Education Management course. This research is a quantitative study with a research sample of 35 people, the data collection technique uses a questionnaire with quantitative description analysis techniques. This research was conducted at the State Christian Religious Institute (IAKN) Kupang. The results showed that the regression coefficient value of the Schoology variable was positive at 0.414 or had an effect of 41.4%. This means that the effect of schoology on independent learning is positive and significant. Increasing schoology will increase students 'learning independent ability and schoology decrease will decrease students' learning independent ability. So that it can be used by students in the learning process